2022
DOI: 10.53808/kus.2008.9.1.0821-l
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton in a Managed Pond in Rajshahi, Bangladesh

Abstract: Twenty one genera of zooplankton were studied based on one year investigation of which 3 genera belonged to Cladocera (19.22%), 5 to Copepoda (36.13%) 12 to Rotifera (44.59%) and 1 to Ostracoda (0.06%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The water supplied by RWASA has a lot of dangerous contaminants. Roy et al (2018) found that the p H of RWASA's water in the chosen areas was within acceptable limits. Additionally, they discovered that odor, turbidity, iron, hardness, and a few others varied from their typical values.…”
Section: Figure 1 Safety Of Drinking Watermentioning
confidence: 80%
“…The water supplied by RWASA has a lot of dangerous contaminants. Roy et al (2018) found that the p H of RWASA's water in the chosen areas was within acceptable limits. Additionally, they discovered that odor, turbidity, iron, hardness, and a few others varied from their typical values.…”
Section: Figure 1 Safety Of Drinking Watermentioning
confidence: 80%